Which sites better represent the sensory function of hands in convalescent stroke patients? A study based on electrophysiological examination - Liu, Yu; Ma, Jiang; Li, Hong; Shi, Wan-ying; Xiao, Zheng-hua; Yang, Qian; Zhao, Qing-qing; Wang, Fang; Tao, Xiao-lin; Bai, Yun-fei (Frontiers in Neuroscience, 2023)
Background: Assessment of hand sensory in stroke patients is necessary, but current clinical assessments are time-consuming and inaccurate. Objective: To explore the nature of light touch sensation and two-point discrimination(2-PD) in convalescent stroke patients’ different sites of hands based on somatosensory evoked potentials (SEP). Methods: The light touch sensation and 2-PD of thumb, index finger, little finger, thenar and hypothenar were measured (n=112) using sensory measurement tools. Then compare the sensory difference among the sites of hand. The SEP and hemiplegic hand function was assessed to evaluate sensory between the SEP and daily living. Results: Sensory function was divided into three levels “sensory intactness”, “sensory impairment” and “sensory loss”. The light touch sensation was main on sensory impairment in finger and palm group. 2-PD of the finger group was mainly sensory loss and the palm group was mainly sensory impairment. There was no statistical difference among each site of the hand in light touch sensation. The correlation coefficient between 2-PD and SEP N20 amplitude were different. The correlation coefficient of thenar and hypothenar was smaller and the finger was larger. The light touch sensation and 2-PD in stroke patients were related to the hemiplegic hand function. Conclusion: Any sites of the hand could be selected for the measurement site of light touch sensation. Little finger and the hypothenar maybe the appropriate site when screening the 2-PD. To improve the patient's ability, the patients could be given more sensory stimulation of the finger.